Anneliese's House - Andreas-Salomé, Lou (Boydell & Brewer, Incorporated, 2021)
"Best known now for her involvement with Nietzsche, Rilke, and Freud, Lou Andreas-Salomé (1861-1937) first became famous for fiction and criticism that engaged provocatively with "the women question." In recent years, the author's treatment of the challenges facing women in a patriarchal society have awakened renewed interest. Anneliese's House is the first English translation of her last and most masterful work of fiction, the 1921 novel Das Haus: Eine Familiengeschichte vom Ende vorigen Jahrhunderts (The House : A Family Story from the End of the Nineteenth Century). Anneliese Branhardt, the book's protagonist, long ago renounced a career as a pianist to raise a family with her physician husband, Frank. She worries about her son Balduin-an aspiring poet modeled on Rilke-and about her equally free-spirited daughter Gitta. She is haunted by memories of a daughter who died in childhood and anxious about a risky, late pregnancy. With her domestic harmony threatened by her own stirrings of autonomy and her children's growing independence, Anneliese finds the future both frightening and promising. The edition is fully annotated, with a critical introduction and bibliography"--